Empowering MSMEs through the Development of Food Courts Based on Location Strategy and Community Collaboration - Dewi, Anita Sumelvia; Syahputra, Erwin (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2025)
Backgrounds: Community service is a crucial dimension of impactful academic work, complementing teaching and research by providing practical solutions to real societal issues. One prominent challenge faced by MSME actors in Sumbercangkring Village, Gurah Subdistrict, Kediri Regency, is the lack of strategic, comfortable, and accessible business locations. Many local entrepreneurs struggle to secure proper trading spaces, while the village possesses untapped potential in the form of a spacious parking area owned by Mr. Erwin, located along a busy main road. Objectives: This community service initiative was conducted to assist in designing a feasible food court model from marketing and management perspectives, strengthen MSME capacity in branding, promotion, and operational management, and build collaborative community involvement to support the establishment of a sustainable culinary centre. Methodology: The implementation methods included initial observation, MSME needs mapping, focus group discussions, marketing strategy mentoring, tenant management training, and the development of a comprehensive food court blueprint. Findings: The results indicate that the food court initiative provides an effective strategic solution for MSMEs by offering a representative business location, increasing collective brand visibility, and enabling marketing synergy among tenants. Conclusions: The community-based food court demonstrates strong potential as a sustainable MSME marketing hub. To ensure long-term sustainability, the programme should be further developed through partnership schemes, community-based branding, and collaborative village business models.